Successful adaptation of a research methods course in South America - Leonardo Tamariz; Diego Vasquez; Cecilia Loor; Ana Palacio (Medical Education Online, 2017)
Background: South America has low research productivity. The lack of a structured research curriculum is one of the barriers to conducting research. Objective: To report our experience adapting an active learning-based research methods curriculum to improve research productivity at a university in Ecuador. Design: We used a mixed-method approach to test the adaptation of the research curriculum at Universidad Catolica Santiago de Guayaquil. The curriculum uses a flipped classroom and active learning approach to teach research methods. When adapted, it was longitudinal and had 16-hour programme of in-person teaching and a six-month follow-up online component. Learners were organized in theme groups according to interest, and each group had a faculty leader. Our primary outcome was research productivity, which was measured by the succesful presentation of the research project at a national meeting, or publication in a peer-review journal. Our secondary outcomes were knowledge and perceived competence before and after course completion. We conducted qualitative interviews of faculty members and students to evaluate themes related to participation in research. Results: Fifty university students and 10 faculty members attended the course. We had a total of 15 groups. Both knowledge and perceived competence increased by 17 and 18 percentage points, respectively. The presentation or publication rate for the entire group was 50%. The qualitative analysis showed that a lack of research culture and curriculum were common barriers to research. Conclusions: A US-based curriculum can be successfully adapted in low-middle income countries. A research curriculum aids in achieving pre-determined milestones. Abbreviations: UCSG: Universidad Catolica Santiago de Guayaquil; UM: University of Miami